Nestling telomere length does not predict longevity, but covaries with adult body size in wild barn swallows - Caprioli, Manuela (The Royal Society, 2013)
Telomere length and dynamics are increasingly scrutinized as ultimate determinants of performance, including age-dependent mortality and fecundity. Few studies have investigated longevity in relation to telomere length (TL) in the wild and none has analysed longevity in relation to TL soon after hatching, despite the fact that telomere shortening may mostly occur early in life. We show that TL in nestling barn swallows (Hirundo rustica) in the wild does not predict longevity. However, TL positively covaries with body size, suggesting that individuals with large TL can afford to grow larger without paying the cost of reduced TL, and/or that benign rearing conditions ensure both large body size and low rates of telomere shortening. Overall, our study hints at a role of TL in developmental processes, but also indicates a need for further analyses to assess the expectation that TL in young individuals predicts longevity in the wild.